Lessons learned after 20 years' experience with penile fracture - Barros,Rodrigo (2020)
ABSTRACT Objective: To report our experience over the past 20 years in the diagnosis and surgical treatment of penile fracture (PF). Materials and methods: Between January 1997 and January 2017, patients with clinical diagnosis of PF were admitted to our facility and retrospectively assessed. Medical records were reviewed for clinical presentation, etiology and operative findings. Postoperative complications, sexual and urinary function were evaluated. Results: Sexual trauma was the main etiological factor, responsible for 255 cases (88.5%): 110 (43.1%) occurred with the “doggy style” position, 103 (40.3%) with “man on top” position, 31 (12.1%) with the “woman on top” position and 11 (4.3%) in other sexual positions. The most common findings in the clinical presentation were hematoma, in all cases and detumescence in 238 (82.6%). Unilateral corpus cavernosum injuries were found in 199 (69%) patients and bilateral in 89 (31%) patients. Urethral injuries were observed in 54 (18.7%) cases. Nine (14.7%) patients developed erectile dysfunction and eight (13.1%) had penile curvature. Only two (3.7%) patients had complications after urethral reconstruction. Conclusions: PF has typical clinical presentation and no need for additional tests in most cases. Hematoma and immediate penile detumescence are the most common clinical findings. Sexual activity was the most common cause. The ‘doggy style’ and ‘man-on-top’ was the most common positions and generally associated with more severe lesions. Concomitant urethral injury should be considered in cases of highenergy trauma. Surgical reconstruction produces satisfactory results, however, it can lead to complications, such as erectile dysfunction and penile curvature.